2020
DOI: 10.1159/000506699
|View full text |Cite
|
Sign up to set email alerts
|

Automated Remote Monitoring for Peritoneal Dialysis and Its Impact on Blood Pressure

Abstract: Introduction: Peritoneal dialysis (PD) provides a safe, home-based continuous renal replacement therapy for patients. The adherence of the patients to the prescribed dialysis fluids cannot always be monitored by physicians. Remote monitoring automated peritoneal dialysis (RM-APD) can affect patients' compliance with treatment and, thus, clinical outcomes. Objective: We aimed to evaluate the clinical outcomes of patients with a remote access program. Methods: This was an observational study. We analyzed the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…However, the overall non-adherence rates to peritoneal dialysis prescription were 2.6% to 85% in the literature, and non-adherence to APD prescription was reported to be 5% to 20% 23,24 . It has been shown that dialysis prescription adherence became more than 90% with the use of RM-APD 7,25 . This platform enables patient treatment data, including peritoneal volume, alerts during treatment, drainage problems, interruption of therapy, loss of dwell time, loss of therapy time to receive, and transmission through to the PD center 7,9 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the overall non-adherence rates to peritoneal dialysis prescription were 2.6% to 85% in the literature, and non-adherence to APD prescription was reported to be 5% to 20% 23,24 . It has been shown that dialysis prescription adherence became more than 90% with the use of RM-APD 7,25 . This platform enables patient treatment data, including peritoneal volume, alerts during treatment, drainage problems, interruption of therapy, loss of dwell time, loss of therapy time to receive, and transmission through to the PD center 7,9 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that dialysis prescription adherence became more than 90% with the use of RM-APD 7,25 . This platform enables patient treatment data, including peritoneal volume, alerts during treatment, drainage problems, interruption of therapy, loss of dwell time, loss of therapy time to receive, and transmission through to the PD center 7,9 . It has provided many opportunities, such as instant monitoring of treatment adherence, early detection of problems, and resolving most of the problems remotely without admitting to the hospital 9,26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 We previously demonstrated that RM-APD provided improvement of dialysis adherence, increased ultrafiltration and better blood pressure control. 13 Poor compliance to dialysis prescription is a common problem in patients with PD, and it is associated with decreased long-term technical survival and increased morbidity and mortality. 14 RPM-APD allows to maintain a better compliance to treatment prescription and increase patient's responsibility and participation in the maintenance of dry weight and as a consequence, blood pressure control.…”
mentioning
confidence: 99%
“…Information such as fill volumes, alerts during treatment, drainage problems, interruption of therapy and blood pressure not within range together with prescription adjustments are continuously exchanged without the need of in person visits to the hospital 11,12 . We previously demonstrated that RM‐APD provided improvement of dialysis adherence, increased ultrafiltration and better blood pressure control 13 …”
mentioning
confidence: 99%